Pendampingan UMKM Cilor Maklor di Desa Argomulyo dalam Pencatatan Keuangan Sederhana dan Digitalisasi Marketing - Wulan Noer Hidayati; Ratri Paramitalaksmi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economic development. However, many MSMEs still face challenges in managing financial records and adapting to digital marketing, including the Cilor Maklor MSME in Argomulyo Village. The Cilor Maklor MSME in this location is one of the micro-enterprises that requires capacity building in both aspects. The main objective of this community service is to assist the Cilor Maklor MSME in understanding and implementing simple financial record-keeping methods and in improving its marketing capabilities through digital marketing, so that the MSME can adapt to current developments and expand its market reach. The method used in this activity includes three stages, namely: 1) MSME Survey, 2) Training and Mentoring, and 3) Evaluation. The results of the community service show an increase in MSMEs' knowledge, understanding, and skills in recording simple financial reports and in marketing products through digital platforms. In addition, this community service activity also has a positive impact on business capacity development and the sustainability of MSMEs.